2005
DOI: 10.1021/ac048217p
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Layer Chromatography and Mass Spectrometry Coupled Using Desorption Electrospray Ionization

Abstract: Desorption electrospray ionization (DESI) was demonstrated as a means to couple thin-layer chromatography (TLC) with mass spectrometry. The experimental setup and its optimization are described. Development lanes were scanned by moving the TLC plate under computer control while directing the stationary DESI emitter charged droplet plume at the TLC plate surface. Mass spectral data were recorded in either selected reaction monitoring mode or in full scan ion trap mode using a hybrid triple quadrupole linear ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
183
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(187 citation statements)
references
References 12 publications
3
183
0
Order By: Relevance
“…Variation of the electrospray voltage showed a maximum response at 4.0 kV, with a range of values greater than 3.0 kV providing adequate response (see Supplementary material, Figure S3). While the results for nebulizing gas pressure and electrospray voltages are typical for both standard electrospray experiments and DESI analyses [5], the optimal flow rate of 10 L/min concurred with several values reported for DESI [7,17], but was higher than others performed with lower flow rates of only 2-5 L/min [5,12]. As discussed in the previous section, this optimal flow rate is likely an artifact of the chosen geometry and would be reduced if the geometry were more compact.…”
Section: Electrospray Variablessupporting
confidence: 81%
“…Variation of the electrospray voltage showed a maximum response at 4.0 kV, with a range of values greater than 3.0 kV providing adequate response (see Supplementary material, Figure S3). While the results for nebulizing gas pressure and electrospray voltages are typical for both standard electrospray experiments and DESI analyses [5], the optimal flow rate of 10 L/min concurred with several values reported for DESI [7,17], but was higher than others performed with lower flow rates of only 2-5 L/min [5,12]. As discussed in the previous section, this optimal flow rate is likely an artifact of the chosen geometry and would be reduced if the geometry were more compact.…”
Section: Electrospray Variablessupporting
confidence: 81%
“…A natural products example is the analysis of an HPTLC separation of glycosphingolipids by IR-MALDI-MS (Distler et al 2008). DESI-MS is a relatively new technique that can also be combined with HPTLC (Takáts et al 2004;Van Berkel et al 2005). Additionally DESI-MS allows for the first time, the direct probing of analytes in intact living plants by MS under ambient conditions without any sample preparation.…”
mentioning
confidence: 99%
“…Desorption electrospray ionisation (DESI) was demonstrated as a means of coupling TLC with mass spectrometry. Development lanes were scanned by moving the TLC plate under computer control while directing the stationary DESI emitter charged droplet plume at the TLC plate surface [16]. Surface-activated chemical ionisation versus electrospray ionisation in the study of selected aluminium (III)/ligand solution equilibria has also been demonstrated [17].…”
Section: Introductionmentioning
confidence: 99%